Small-molecule probes elucidate global enzyme activity in a proteomic context - Lee, Jun-Seok; Yoo, Young-Hwa; Yoon, Chang No (KOREAN SOCIETY BIOCHEMISTRY & MOLECULAR BIOLOGY, 2014)
The recent dramatic improvements in high-resolution mass spectrometry (MS) have revolutionized the speed and scope of proteomic studies. Conventional MS-based proteomics methodologies allow global protein profiling based on expression levels. Although these techniques are promising, there are numerous biological activities yet to be unveiled, such as the dynamic regulation of enzyme activity. Chemical proteomics is an emerging field that extends these types proteomic profiling. In particular, activity-based protein profiling (ABPP) utilizes small-molecule probes to monitor enzyme activity directly in living intact subjects. In this mini-review, we summarize the unique roles of small-molecule probes in proteomics studies and highlight some recent examples in which this principle has been applied.
Keywords: SPECTROMETRY-BASED PROTEOMICS; MASS-SPECTROMETRY; QUANTITATIVE PROTEOMICS; GEL-ELECTROPHORESIS; HUMAN GENOME; PROTEIN; IDENTIFICATION; INHIBITORS; DISCOVERY; CHEMISTRY